The role of political buzzers in the formation of public opinion supports Anies Baswedan on social media Twitter - Harry Fajar Maulana, Harry Fajar Maulana; Wa ode Mutmainah, Wa ode Mutmainah; Nur Tang, Nur Tang (COMMICAST, 2022)
This article will elaborate on the role of buzzers in the establishment of public opinion on social media through twitter platform by taking the keyword Support Anies Baswedan in the 2024 election. The purpose of this study is to find out the actors involved in the formation of opinions in support of Anies Baswedan in the 2024 election and the extent of the network that has been created by buzzers. This paper uses a qualitative approach using Social Network Analytic (SNA) from Netlytic.org in the analysis of buzzer actors in the formation of public opinion Supporting Anies Baswedan in Persidn 2024. The results showed that from 1156 Tweet data occurred from November 27, 2021 to December 05, 2021, a total of 1159 Massages and Unique Poster 849 were found to have 150 accounts created in 2021 on the issue of Supporting Anies Baswedan, 10 accounts that commented and shared tweets for up to 05 Decesember.